A STUDY OF CULTURAL ASPECTS IN ARABIC TEXTBOOKS FOR MADRASAH ‘ALIYAH IN BANTEN - Moh. Nur Arifin (Saintifika Islamica, 2016)
The teaching of culture is considered to be an important part of teaching foreign language i.e. Arabic, since one major aim of language teaching is to increase the understanding and tolerance between cultures. As a result, it is very reasonable to say that learning a language is also learning culture of native speakers. Teaching a new language will accordingly inevitably involve teaching a new culture. Only through introducing and developing understanding of the culture of the target language will a language learner be able to function properly in the target language. In teaching Arabic as Foreign Language (AFL), textbooks play an important role in today’s school world since most of Arabic teachers of SMA/MA in Indonesia use them as the most important tool and teaching resources. The purpose of this research are (1) to describe authors’ awareness to insert cultural elements into the selected texbook of Bahasa Arab (BA) X, XI and XII and تعهٛى انهغت انعسبٛت Pelajaran Bahasa Arab (PBA) X, XI, XII as materials for teaching and learning Arabic, (2) to identify what cultural aspects are included in the Arabic textbooks currently used by Madrasah Aliyah in Serang, (3) to identify the patterns of insertion of these cultural aspects in the Arabic textbooks used. As the method of research, the researcher used content analysis. The data is selected taxtbook of تعليماللغة العربية , Pelajaran Bahasa Arab Madrasah Aliyah Kelas X, XI, XII writen by Dr. D. Hidayat, Published by PT Karya Toha Putra, Semarang Indonesia, 2013 and Pelajaran Bahasa Arab untuk SMA Kelas X, XI, XII written by Darsono and Sururi Abdul Jalal, published by Pusat Kurikulum dan Perbukuan Kementerian Pendidikan Nasional, 2011 by using Byram (1994:51-52) and Risager (1994: 52-53) criteria i.e. Social identity and social groups, Social interaction, Belief and behavior, Socio-political institutions, Socialization and the life-cycle, National history, National geography, National cultural heritage, Stereotypes and national identity, International and intercultural issue, and Point of view and style of the textbook auhtor (s). The result of this research are that (1) the authors have awareness to insert cultural aspects into the textbook, (2) of the eleven criteria only three of them are not inserted into the textbooks i.e. Social identity and social groups, Social interaction, Belief and behavior, National geography, National cultural heritage, Stereotypes and national identity, International and intercultural issue, and Point of view and style of the textbook auhtor (s), (3) the patterns of insertion of these cultural aspects in the Arabic textbooks are both writings and pictures.